Teaching speaking by using picture strip stories - Reza Novianda (English Education Journal, 2017)
This study was aimed to find out whether picture strip stories used as CLT (Communicative Language Teaching) could significantly help students develop their speaking skills, and also to find out which speaking sub-skills could be better taught by using picture strip stories. This study used a true experimental research design with quantitative and qualitative methods. It had an experimental group (EG) which was taught by using picture strip stories and a control group (CG) which was taught by using a typical speaking drill technique. The subjects of the study were classes VIII.1 and VIII.2 in the second grade at middle school, MTsN Model Gandapura, with 30 students in each class. The instrument used was a speaking test sheet. The collected data was analyzed using SPSS. The findings showed that using picture strip stories in teaching speaking significantly improved the EG students’ speaking scores. The EG average pre-test score  was 60 and for the CG it was 52 while the EG mean post-test score was 80 and for the CG it was 66. The students’ speaking ability in both groups was significantly different as indicated by the t-test (t-obtain (6.79 t-table 2.00). This showed that the students who were taught speaking by using the picture strip story technique improved significantly more in speaking than those who were taught  by using the drill technique. Besides, the findings from the study showed that five speaking sub-skills, viz: pronunciation, grammar, vocabulary, fluency, and comprehensibility, were all better taught by using picture strip stories.